Cyclin D–Cdk4 is regulated by GATA-1 and required for megakaryocyte growth and polyploidization - Muntean, Andrew G. (American Society of Hematology, 2007)
Endomitosis is a unique form of cell cycle used by megakaryocytes, in which the latter stages of mitosis are bypassed so that the cell can increase its DNA content and size. Although several transcription factors, including GATA-1 and RUNX-1, have been implicated in this process, the link between transcription factors and polyploidization remains undefined. Here we show that GATA-1–deficient megakaryocytes, which display reduced size and polyploidization, express nearly 10-fold less cyclin D1 and 10-fold increased levels of p16 compared with their wild-type counterparts. We further demonstrate that cyclin D1 is a direct GATA-1 target in megakaryocytes, but not erythroid cells. Restoration of cyclin D1 expression, when accompanied by ectopic overexpression of its partner Cdk4, resulted in a dramatic increase in megakaryocyte size and DNA content. However, terminal differentiation was not rescued. Of note, polyploidization was only modestly reduced in cyclin D1–deficient mice, likely due to compensation by elevated cyclin D3 expression. Finally, consistent with an additional defect conferred by increased levels of p16, inhibition of cyclin D-Cdk4 complexes with a TAT-p16 fusion peptide significantly blocked polyploidization of wild-type megakaryocytes. Together, these data show that GATA-1 controls growth and polyploidization by regulating cyclin D-Cdk4 kinase activity.